Utilisation of enterobacterial repetitive intergenic consensus (ERIC) sequence-based PCR to fingerprint the genomes of Bifidobacterium isolates and other probiotic bacteria - Shuhaimi, M.; Ali, A.M.; Saleh, N.M.; Yazid, A.M. (Springer, 2001)
Enterobacterial repetitive intergenic consensus based on PCR (ERIC-PCR) was used to generate DNA fingerprints for bifidobacteria and other probiotic bacteria. Two primers (ERIC 1R and ERIC 2) used in ERIC-PCR revealed that all of the probiotic bacteria tested possess enterobacterial repetitive intergenic consensus sequences with the PCR products ranging from 250 bp to 5000 bp. The bacterial strains can be differentiated by comparing fingerprint patterns. The dendrogram of the fingerprints revealed that most of the bifidobacterial wild type strains fell into one cluster at similarity level of approximately 79%.